PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA UPT SD NEGERI 003 MUARA UWAI - Muhammad Depri; Muhammad Syahrul Rizal; Yenni Fitra Surya; Putri Hana Pebriana; Mufarizuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve the critical thinking skills of fourth-grade students of UPT SD Negeri 003 Muara Uwai through the application of the Problem Based Learning (PBL) learning model. This study is a Classroom Action Research (CAR) conducted in two cycles, each consisting of two meetings. The subjects of the study were 15 fourth-grade students. Data collection techniques used observation, tests, and documentation. The instruments used were observation sheets of teacher and student activities and written critical thinking ability tests. The results of the study showed that the application of the PBL model was able to improve students' critical thinking skills. In the pre-action, the percentage of student completion was only 27% with an average score of 48.53. After the application of the PBL model in cycle I, the completion increased to 47% with an average score of 48.75. In cycle II, the completion increased further to 80% with an average score of 71.45. This increase indicates that the PBL model is effective in improving students' critical thinking skills, especially in the indicators of providing simple explanations, building basic skills and concluding, further explanations, and developing strategies and tactics.